Outcome Analysis of Surgical Stabilization of Rib Fractures in Trauma Patients. Issue 1 (January 2019) - Fokin, Alexander A.; Wycech, Joanna; Weisz, Russell; Puente, Ivan
Abstract : Objectives: To compare outcomes in patients with rib fractures (RFX) who underwent surgical stabilization of rib fractures (SSRF) to those treated nonoperatively. Design: Retrospective cohort study. Setting: Two Level 1 Trauma Centers. Patients: One hundred seventy-four patients with multiple RFX divided into 2 groups: patients with surgically stabilized RFX (n = 87) were compared with nonoperatively managed patients in the matched control group (MCG) (n = 87). Intervention: SSRF. Outcome Measurements: Age, sex, injury severity score, RFX, mortality, hospital length of stay (HLOS) and intensive care unit length of stay (ICULOS), duration of mechanical ventilation (DMV), co-injuries, and time to surgery. Patients were further stratified by presence or absence of flail chest and pulmonary contusion (PC). Results: Flail chest, displaced RFX, and PC were present significantly more often in SSRF patients compared with the MCG. Mortality was lower in SSRF group. HLOS and ICULOS were longer in SSRF group compared with the corresponding MCG patients regardless of timing to surgery ( P < 0.01 for all). SSRF patients with flail chest had comparable HLOS, ICULOS, and DMV to MCG patients with flail chest ( P > 0.3 for all). SSRF patients without flail chest had significantly longer HLOS and ICULOS than MCG patients without flail chest ( P < 0.001 for both). Presence of PC did not affect lengths of stay. Conclusions: SSRF patients had reduced mortality compared with nonoperatively managed patients. HLOS, ICULOS, and DMV were longer in SSRF patients than in MCG. When flail chest was present, lengths of stay were comparable. PC did not seem to affect the surgical outcome. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.